2012
DOI: 10.1021/nl3003864
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Metallic Glass Nanowires by Gas Atomization

Abstract: Gas atomization which is a conventional technique in powder metallurgy is adapted for the formation of metallic glass nanowires. This approach is able to produce a large quantity of nanowires with diameters in the 50-2000 nm range. Experiments performed with different conditions and alloy compositions confirm that the key mechanism of the nanowire formation is the spinnability which increases exponentially when the melt stream is supercooled from the liquid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…The unique flow behavior of glasses in undercooled liquid temperature can be utilized to form and shape the viscous liquid into different nanomaterials. This property leads to various methods including hot embossing or imprinting (HI), 1-3 wire drawing, 4,5 gas atomization, 6 and even fracturing the solids, where thin ligaments of metallic glass wires form. 7 Of course, other techniques commonly used for fabricating crystalline wires can also be used for amorphous wires, such as focused ion beam (FIB), where either wires or pillars can be shaped by milling away the rest of the materials outside of the wires using high energy ion beams.…”
mentioning
confidence: 99%
“…The unique flow behavior of glasses in undercooled liquid temperature can be utilized to form and shape the viscous liquid into different nanomaterials. This property leads to various methods including hot embossing or imprinting (HI), 1-3 wire drawing, 4,5 gas atomization, 6 and even fracturing the solids, where thin ligaments of metallic glass wires form. 7 Of course, other techniques commonly used for fabricating crystalline wires can also be used for amorphous wires, such as focused ion beam (FIB), where either wires or pillars can be shaped by milling away the rest of the materials outside of the wires using high energy ion beams.…”
mentioning
confidence: 99%
“…2c. The difference between the red curve and the black curve corresponds to the area of exothermic heat flows, indicating that the products significantly include excessive free volume56.…”
Section: Resultsmentioning
confidence: 99%
“…MG nanowires are promising building blocks for magnetic sensors, battery electrodes, and heterogeneous catalysts1234567. The development for practical applications requires a large amount of the high quality MG wires with low cost.…”
mentioning
confidence: 99%
“…Understanding the characteristics of surface STZs is growing in relevance, particularly within the past five years, as researchers have begun fabricating [14,15] and mechanically * linx@bu.edu † parkhs@bu.edu characterizing bulk metallic glass nanowires [16][17][18]. These experimental studies have revealed enhanced tensile ductility in smaller, volume-confined samples, though the potential role of surface STZs in controlling this nanoscale property has not been investigated.…”
Section: Introductionmentioning
confidence: 99%